Kapitalist üretim sisteminde emeğin varolma mücadelesinin vazgeçilmez aracı: Grev - (:unkn) unknown (My University, 2012)
Grev, emeği metalaştıran işçinin üretim sistemi ve toplumsal düzen olarak kapitalizme karşı geliştirdiği en etkili silahtır. Burjuvazi işçi sınıfının ekonomik ve siyasal mücadelesindeki bu etkili silahı önce reddetmiş; yasaklarla engelleyemeyince grevi tanımış ancak etkisizleştirmek üzere düzenleme yoluna gitmiştir. Tüm engellemelere rağmen grev, kapitalist üretimin sistemi var olduğu sürece işçi sınıfı mücadelesinin en etkili aracı olarak olmaya devam edecektir.

Strike is the most effective tool which worker materializing labor has developed against the capitalism as a production system and social order. At first, the bourgeoisie has refused this effective tool in the economic and political struggle of the proletariat; when they have not been able to prevent through prohibitions, they have accepted the strike; however, they have tried to organize so as to defuse. Despite all of the preventions, the strike will stay on the most effective tool of the struggle of proletariat as long as the system of capitalist production exists.
Indispensable insrtument of struggle for existence of labor in the capitalist production system: Strike
Keywords: Sağlık Politikaları ve Hizmetleri